2009
DOI: 10.1007/s00221-008-1694-0
|View full text |Cite
|
Sign up to set email alerts
|

The amplitude of physiological tremor can be voluntarily modulated

Abstract: The objective of this study was to determine whether it was possible to voluntarily modulate physiological tremor (PT), i.e., reduce its amplitude. We recorded the postural index finger tremor of 30 healthy participants with a laser in four conditions: (A) eyes closed, without any attempt to modulate PT amplitude, (B) no visual feedback, trying to reduce PT amplitude, (C) visual feedback, trying to reduce PT amplitude. For conditions B and C, subjects were asked to avoid using muscle contraction as a means to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 49 publications
1
18
0
Order By: Relevance
“…Past studies have had varying success in finding an effect of augmented visual feedback on tremor. Some studies observed the expected positive correlation (Morrison and Keogh 2001;Carignan et al 2009) but others have not (Stephens and Taylor 1974;Feys et al 2004;Daneault et al 2010).…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…Past studies have had varying success in finding an effect of augmented visual feedback on tremor. Some studies observed the expected positive correlation (Morrison and Keogh 2001;Carignan et al 2009) but others have not (Stephens and Taylor 1974;Feys et al 2004;Daneault et al 2010).…”
Section: Discussionmentioning
confidence: 88%
“…In both experiments 1 and 2, the acceleration power spectra of the computer visual feedback conditions were shifted towards lower frequencies compared to the natural vision condition, which suggests that these feedback conditions involved greater levels of voluntary control (Freund and Hefter 1993). This effect has been attributed to increased synchronization at the motor unit (Carignan et al 2009), cortex (Babiloni et al 2004), and cerebellum (Houweling et al 2008) levels during finger movements that require attention under visual feedback.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations